2003
DOI: 10.4049/jimmunol.171.9.4512
|View full text |Cite
|
Sign up to set email alerts
|

Thymocyte Sensitivity and Supramolecular Activation Cluster Formation Are Developmentally Regulated: A Partial Role for Sialylation

Abstract: TCR reactivity is tuned during thymic development. Immature thymocytes respond to low-affinity self-ligands resulting in positive selection. Following differentiation, T cells no longer respond to low-affinity ligands, but respond well to high-affinity (foreign) ligands. We show in this study that this response includes integrin activation, supramolecular activation cluster formation, Ca2+ flux, and CD69 expression. Because glycosylation patterns are known to change during T cell development, we tested whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 64 publications
5
44
2
Order By: Relevance
“…As reported previously (20,27,39), we find that these animals show normal representation of major thymocyte populations, but have a severe reduction in peripheral CD8 ϩ T cells (Fig. 3, A and B).…”
Section: St3gal-i Deficiency Does Not Alter the Pattern Of Cd8 Noncogsupporting
confidence: 65%
See 2 more Smart Citations
“…As reported previously (20,27,39), we find that these animals show normal representation of major thymocyte populations, but have a severe reduction in peripheral CD8 ϩ T cells (Fig. 3, A and B).…”
Section: St3gal-i Deficiency Does Not Alter the Pattern Of Cd8 Noncogsupporting
confidence: 65%
“…This susceptibility to cell death was lost as thymocytes matured to the CD8 SP stage, and it was proposed that regulation of CD8 noncognate binding by altered sialylation may be responsible for these changes in mature thymocyte sensitivity (38). In keeping with this last point, we and others showed that both enzymatic desialylation and ST3Gal-I deficiency can enhance sensitivity of mature T cells to low affinity peptide/MHC ligands (39,40). Furthermore, neuraminidase treatment can promote induction of apoptosis following T cell activation through the TCR (41).…”
supporting
confidence: 49%
See 1 more Smart Citation
“…These findings, combined with normal TD humoral responses in 3d mice (this study) and the lack of T cell population changes in nonautoimmune 3d mice (21), suggest that 3d T cells compensate for the slightly reduced function of 3d APCs. Possible explanations for this are dynamic tuning of T cells for which a large number of different molecular mechanisms have been identified, including cell signaling feedback, level of CD5 expression, sialylation, and miRNA expression (36)(37)(38)(39)(40), or modification of the T cell receptor repertoire. We are currently generating T cell receptor transgenic 3d mice to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the conversion of the peanut agglutinin (PNA) 5 high (PNA high ) phenotype of immature CD4/CD8 medullary thymocytes to the PNA low phenotype of the mature singlepositive CD8 and CD4 thymocytes results from conversion of the PNA ligand, the O-linked glycan Gal␤1-3GalNAc␣Thr/Ser, to its sialylated form, NeuAc␣2-3Gal␤1-3GalNAc␣Thr/Ser, that is no longer recognized by PNA due to increased expression of a sialyltransferase, ST3Gal I (1-4). In CD8 T cells, this glycosylation change reduces the affinity of CD8 for MHC class I, suggesting that sialylation of CD8 O-glycans modulates CD8 function during selection and maturation of CD8 T cells (5)(6)(7). Naive CD8 cells of ST3Gal I null mice that are constitutively PNA high undergo rapid apoptosis in the periphery, reducing the CD8 population to 10% of wild type (2).…”
Section: Activation Of Murine Cd4 ؉ and Cd8 ؉ T Lymphocytes Leads To mentioning
confidence: 99%